2022
DOI: 10.1002/adfm.202204931
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Micromorphological Effects of Cation Disordering on Co‐Free Layered Oxide Cathodes

Abstract: Controlling Li/Ni disordering has always been a priority in designing Co‐free layered oxide cathodes. The Li/Ni disordering is an atomic‐scale structural defect that has been extensively studied by macroscopic statistical characterizations. Significantly less is known about its microstructure in the layered structure and correlations with electrochemical performance. In this work, combining multiscale structural characterizations, it is found that Li/Ni disordering surprisingly takes various microstructural fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The highest intensity ratio of (003)/(104) appears at 750 °C, so the NM90 cathode prepared at this temperature (labeled as NM90 following) is considered to have the lowest Li/Ni intermixing degree. [ 27,34 ] The XRD Rietveld refinement results in Figure 1 a and Table S1 (Supporting Information) indicate that the NM90 can be indexed as a typical layered phase and has a Li/Ni intermixing of 6.7%. As the magnetic frustration cannot be alleviated, the Li/Ni intermixing is inevitably high in Co‐free cathodes, and it is noteworthy that Mn is not a necessary cause of Li/Ni intermixing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest intensity ratio of (003)/(104) appears at 750 °C, so the NM90 cathode prepared at this temperature (labeled as NM90 following) is considered to have the lowest Li/Ni intermixing degree. [ 27,34 ] The XRD Rietveld refinement results in Figure 1 a and Table S1 (Supporting Information) indicate that the NM90 can be indexed as a typical layered phase and has a Li/Ni intermixing of 6.7%. As the magnetic frustration cannot be alleviated, the Li/Ni intermixing is inevitably high in Co‐free cathodes, and it is noteworthy that Mn is not a necessary cause of Li/Ni intermixing.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the conventional Mn stabilization mechanism, the inevitable Li/Ni intermixing caused by the removal of Co is another potential origin of lattice oxygen and structure stability in Co-free Ni-rich cathodes. [24][25][26] For example, Lu et al reported that when the Li/Ni intermixing is increased from 4.20% to 4.85% in LiNi 0.85 Mn 0.15 O 2 , the cycling stability is significantly improved from 88.4% to 96.2% after 100 cycles at 0.5 C. [27] Further, the surface reconfiguration layer induced by the Li/Ni intermixing have also been reported to enhance the structural stability of LiNi 0.8 Mn 0.1 Co 0.1 O 2 . [28] In these reports, the Li/Ni intermixing configuration is also defined as Ni-O-Ni super-exchange chains, and it is generally accepted that the intermixed Ni ions play a pillar function in the Li layer to mitigate the structure collapse.…”
Section: Introductionmentioning
confidence: 99%
“…These microstructural features have a significant impact on their electrochemical performances and the corresponding information has been summarized in detail. 62 As shown in Fig. 8d–g, the as-prepared LiNi 0.85 Mn 0.15 O 2 samples were determined and their structures and differences were compared using the HEXRD method.…”
Section: Materials Synthesis and Structure Studies Of Drx Cathodesmentioning
confidence: 99%
“…The worldwide low-carbon strategy has driven the expeditious development of lithium-ion power batteries (LIBs), and the research of Co-free high energy density LiNi x Mn 1– x O 2 (NM) has attracted more care as a result of the issues of humanity and ecology caused by cobalt resources. ,,, Recent literature has reported that NM cathode material would exhibit higher thermal stability than NCM; however, it suffers from poor rate capacity and larger Li/Ni cation disorder as a result of magnetic resistance between Ni 2+ /Ni 3+ and Mn 4+ . …”
Section: Introductionmentioning
confidence: 99%